CO2/Propylene Oxide Copolymerization with a Bifunctional Catalytic System Composed of Multiple Ammonium Salts and a Salen Cobalt Complex Containing Sulfonate Anions - Seo, Yeong Hyun; Hyun, Yong Bin; Lee, Hyun Ju; Lee, Hong Cheol; Lee, Jung Hyun; Jeong, Sun Mi; Lee, Bun Yeoul (Macromolecular Research, 2021)
A (Salen)Co(III) complex tethering four quaternary ammonium salts with covalent bonds is one of the most highly active catalysts for CO2/epoxide copolymerization. In this work, we aimed to prepare similar (Salen)Co(III) complexes to which quaternary ammonium salts are linked via ionic interactions. Thus, multiple ammonium salts containing 2–5 quaternary ammonium salt units and (Salen)Co(III) complexes containing one or two -SO3−[PhNH3]+ moieties were prepared. A binary catalytic system composed of the prepared multiple ammonium salts and the prepared (Salen)Co(III) complex containing -SO3−[(nBu)4N]+ moieties showed high activity (TOF, 1500-4500 h−1) for CO2/propylene oxide (PO) copolymerization, whereas a combination of the multiple ammonium salts and the conventional (Salen)Co(III) complex not containing -SO3−[(nBu)4N]+ moieties was inactive under the identical polymerization conditions of [PO]/[Co] = 20000. However, a substantial amount of cyclic carbonate was concomitantly generated, especially when a (Salen)Co(III) complex containing two -SO3−[(nBu)4N]+ moieties was used (25–30%). This side-reaction could be mitigated by ca. 50% by employing a (Salen)Co(III) complex containing one -SO3−[(nBu)4N]+ moiety. Cyclic carbonate generation can reasonably be ascribed to ammonium salts ([(nBu)4N]+[carbonate]−) not linked to the (Salen)Co(III) complex formed in the binary catalytic system.[Figure not available: see fulltext.].
Keywords: Ammonium salt; Bifunctional catalysts; CO2/propylene oxide copolymerization; Cobalt complexes; Cobalt complexes (III); Copolymerisation; Multiple quaternary ammonium salt; Propylene oxide; Quaternary ammonium salt; Salen cobalt complex; bifunctional catalyst; CO2/propylene oxide copolymerization; multiple quaternary ammonium salt; salen cobalt complex